Functional communication training with and without extinction and punishment. - Fisher, W (1993)
Functional communication training has been reported to be a promising treatment for severe behavior problems. In this study, functional communication training alone and combined with extinction and/or punishment was evaluated for 4 clients with severe retardation, behavior problems, and communication deficits. The participants were inpatients on a hospital unit for treatment of severe behavior disorders. They received individualized interventions based on functional assessment that included reinforcement of a communication response with the same function as their destructive behavior. Results showed that for some patients, functional communication training was not sufficient to produce clinically significant reductions in destructive behavior, and the combination of training plus punishment produced the largest and most consistent reductions.